Isolation of Staphylococcus aureus from ear swab in Iraqi children as a causative agent of Otitis externa - Eman A. Al-Hasnawi (مجلة كلية الطب, 2017)
Background: Staphylococcus aureus is a Gram-positive, spherical, grape like clusters arrangment bacterium, non-spore forming. Is a genus that causes many hard diseases such as food poisoning, gastroenteritis with severe symptoms. S. aureus is commonly found in the wide environment (soil, air and water) and is importantly found in the nose and skin in the humans. And can causes ear infection by entering the ear. The diagnosis of Otitis externa is usually made clinically and bacterial tests. Objective: To detection and isolation of the bacteria Staphylococcus aureus from pus specimens of ear swab, among Iraqi children with Otitis externa. Patients and methods: Eighty ear swab specimens from suspected cases of Otitis externa among children, inoculated to brain heart broth, then to non-selective media (blood agar) and when growth appeared, cultured on selective media (Mannitol salt agar) plates in the laboratory. The plates were incubated at 37ᵒC aerobically for 24 hours, identified the isolate by Gram stain, catalase and coagulase of human plasma. Results: In this study, from 80 samples (43) males; (37) female, with (31) cases had medical history controlled by 20 healthy individuals: the bacterial growth and identification on blood agar resulted in presence of nonspecific bacteria in (65) samples, were (36) males and (29) females, while specific bacteria Staphylococcus aureus on selected media (Manitol salt agar), catalase positive and Co-agulase positive, were in (28) samples of (16) males and (12) females most of them in age (1-3) years, were (11) samples, in males more than females. Conclusion: The isolation of Staphylococcus aureus was the most important diagnosis of predominant causative agents of Otitis externa among Iraqi children and showed such an exhibition about the epidemic